THE EFFECT OF VERMICOMPOST ON THE GROWTH OF SOYBEAN (Glycine max L.) - Sri Pratiwi Aritonang (International Journal of Ecophysiology, 2020)
The growth and production of soybean (Glycine max L) fertilized by vermicompost was conducted. The vermicompost used consisted of 4 levels, namely: K0 = no vermicompost, K1 = 60 g, K2 = 90 g and K3 = 120 g, each treatment was replicate 3 times. The results showed that the dose of vermicompost significantly affected to the number of branches, number of pods and seed weight, however the organic vertilizer not significantly affected on plant height, flowering age, number of empty pods and seeds dry weight. The interaction dose of vermicompost has no significant effect on plant height, number of branches, flowering age, number of pods, number of filled pods, number of seed and 100 seeds dry weight.